Increasing of the accuracy of determining the coordinates of an aerial object in the two-position network of small-sized radars - Khudov, Hennadii; Berezhnyi, Andrii; Oleksenko, Oleksandr; Maliuha, Volodymyr; Balyk, Ivan; Herda, Maksym; Sobora, Anatolii; Bridnia, Yehor; Chepurnyi, Viacheslav; Gridina, Valentina (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research is the process of determining the coordinates of aerial objects by a small-sized radars. The main hypothesis of the study assumes that combining two small-sized radars into a network could improve the accuracy of determining the coordinates of aerial objects. It was established that when determining the coordinates of an aerial object by a small-sized radars, the accuracy of determining the range is much better than the accuracy of determining the angular coordinate. To eliminate this shortcoming, a two-position network of small-sized radars and their error ellipses was considered. It is proposed to use the range-finding method in each small-sized radar station of the two-position network. A method for determining the coordinates of aerial objects in a two-position network of small-sized radars has been improved, which, unlike known ones: – enables a synchronous survey of the airspace by small-sized radars; – measures the range to the aerial object by two small-sized radars; – determines the coordinates of the aerial object by the joint processing of radar information from two small-sized radars. The accuracy of determining the coordinates of aerial objects in a two-position network of small-sized radars was evaluated. The experimental evaluation was carried out by means of simulation using the method of Monte Carlo statistical tests. Working areas of the two-position network of small-sized radars were calculated. It was established that the two-position network of small-radars works only in the area formed by the intersections of the viewing areas of small-sized radars during their autonomous operation.